Paper as Image. (London : Arts Council of Great Britain, 1983)
Amat, Frederic ; Anker, Suzanne ; Barker, Laurence ; Caro, Anthony ; Clark, Kathryn ; Close, Chuck ; Corstiaensen, Boudewijn ; Echarri, Isabel ; Fisher, Joel ; Genn, Nancy ; Greenwald, Caroline ; Hill, Clinton ; Hockney, David ; Kawaguchi, Tatsuo ; Kraayeveld, Carla ; Kyle, Heidi ; Kyle, Hugh ; Lewis, Golda ; Lutz, Winifred ; Noland, Kenneth ; Nugent, Robert ; Pietsch, Heinz dieter ; Rauschenberg, Robert ; Royce, Richard ; Schmidt, Joyce ; Shields, Alan ; Siegenthaler, Fred ; Smith, Richard ; Stuart, Michelle ; Turner, Silvie ; Tyson, Ian ; Wong, Paul
biografie
Paper as Image, Tour: Sunderland Arts Centre, Sunderland, 22 January - 19 February 1983 ; Kettle's Yard, Cambridge, 5 March - 10 April ; Bangor Oriel Art Gallery, 19 April - 21 May ; Midland Group Nottingham, 28 May - 3 July ; Southampton Art Gallery, 9 July - 14 August ; To be confirmed, 20 August - 25 September ; Gardner Arts Centre Brighton, 1-30 October ; Crafts Council Gallery, London, 9 November - 24 December 1983
English
kunstcatalogus